Reviewing the effects of the separation of heritage and the succession of the spouse - Castillo Freyre, Mario (2018)
In this article an analysis is made of the effects of the separation of assets and the succession of the spouse. The traditional idea is that when two people marry, they must not only unite their lives in extra-patrimonial aspects, but also in those of patrimonial order. The community society has as its central objective that the bulk of the goods acquired in the future, with certain exceptions, be considered as common goods. In that sense, it implies that, from the moment of the celebration of marriage, the generality of goods acquired by the spouses, in strict, will not be the property of each one of them, but of the community of acquisitions. In this way, no matter how much a single person acquires a good, such good will not belong to him, but to the so-called community of acquisitions, and will have the quality of a common good legally distinct from the patrimony of each one of them.  What is proposed in this article is that the regime of separation of assets may undergo a legislative amendment, which implies adding an option to it, which would consist in the separation of assets to be maintained after the death of the owner of said patrimony. This means that, in choosing this path, the spouses could agree to marry under separation of patrimonies and also to renounce each other.